Chasing the Ghost: Hyperinflammation Does Not Cause Sepsis - Shapiro, Leland; Scherger, Sias; Franco-Paredes, Carlos; Gharamti, Amal A.; Fraulino, David; Henao-Martinez, Andrés F. (Frontiers in Pharmacology, 2022)
Sepsis is infection sufficient to cause illness in the infected host, and more severe forms of sepsis can result in organ malfunction or death. Severe forms of Coronavirus disease-2019 (COVID-19), or disease following infection with severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) are examples of sepsis. Following infection, sepsis is thought to result from excessive inflammation generated in the infected host, also referred to as a cytokine storm. Sepsis can result in organ malfunction or death. Since COVID-19 is an example of sepsis, the hyperinflammation concept has influenced scientific investigation and treatment approaches to COVID-19. However, decades of laboratory study and more than 100 clinical trials designed to quell inflammation have failed to reduce sepsis mortality. We examine theoretical support underlying widespread belief that hyperinflammation or cytokine storm causes sepsis. Our analysis shows substantial weakness of the hyperinflammation approach to sepsis that includes conceptual confusion and failure to establish a cause-and-effect relationship between hyperinflammation and sepsis. We conclude that anti-inflammation approaches to sepsis therapy have little chance of future success. Therefore, anti-inflammation approaches to treat COVID-19 are likewise at high risk for failure. We find persistence of the cytokine storm concept in sepsis perplexing. Although treatment approaches based on the hyperinflammation concept of pathogenesis have failed, the concept has shown remarkable resilience and appears to be unfalsifiable. An approach to understanding this resilience is to consider the hyperinflammation or cytokine storm concept an example of a scientific paradigm. Thomas Kuhn developed the idea that paradigms generate rules of investigation that both shape and restrict scientific progress. Intrinsic features of scientific paradigms include resistance to falsification in the face of contradictory data and inability of experimentation to generate alternatives to a failing paradigm. We call for rejection of the concept that hyperinflammation or cytokine storm causes sepsis. Using the hyperinflammation or cytokine storm paradigm to guide COVID-19 treatments is likewise unlikely to provide progress. Resources should be redirected to more promising avenues of investigation and treatment.